Pap test in rural women (Research, Society and Development, 2023)
The Ministry of Health recommends that every woman who has or has had sexual activity should undergo periodic preventive examination (cytopathological - CP). The objective of this study was to find out what could be an impediment for rural women in a small municipality in the interior of the state of Rio Grande do Sul to take the exam. An exploratory and field qualitative and quantitative research was carried out, with individual questionnaires with open and closed questions. Seventy-five women living in rural areas who had not undergone the cytopathological examination for more than a year were included. The research followed the precepts of Resolution 466/2012, of the National Health Council. Quantitative data were distributed into frequencies. And the qualitative data were categorized. Of the 75 women interviewed, 52% performed CP collection every 2 years and the minority, 38.75% never performed this exam. This number shows that this is a small portion of women in a municipality with more than 11,000 (eleven thousand) inhabitants. However, it is worth mentioning that most of these live farther from the Family Health Strategies (ESF). We conclude that women who have never taken the PC exam are those who live in more distant regions in the rural area, who do not have their own means of transport and are low-income. Thus, nursing interventions aim to encourage the examination of PC even in the most remote areas to increase the chances of cure.